Analysis of tirzepatide in the US FDA adverse event reporting system (FAERS): a focus on overall patient population and sex-specific subgroups - Ou, Yingyong; Cui, Zhiwei; Lou, Siyu; Zhu, Chengyu; Chen, Junyou; Zhou, Linmei; Zhao, Ruizhen; Wang, Li; Zou, Fan (Frontiers in Pharmacology, 2024)
Objective: Tirzepatide, a novel GIP and GLP1 agonist, has been extensively examined in clinical trials. However, specific data on its adverse drug events (ADEs) remain limited. This study aims to comprehensively assess real-world ADEs associated with tirzepatide by mining data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database.Methods: ADE reports from the FAERS database were retrieved for the second quarter of 2022 through the first quarter of 2024. Significant associations between ADEs and tirzepatide were evaluated using proportional disproportionality analyses, including the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item GammaResults: A total of 37,827 ADE reports associated with tirzepatide were identified, with 100 significantly disproportionate preferred terms (PTs) recognized by all four algorithms. The top five PTs with the highest reporting rates were incorrect dose administered, injection site pain, off-label use, nausea, and injection site hemorrhage.Additionally, unexpected signals such as starvation ketoacidosis were identified. The median time to onset for all ADEs was 23 days. Furthermore, sexgender-specific high-intensity signals were found, with males primarily experiencing gastrointestinal disorders and females experiencing general disorders and administration site conditions.This study provides valuable insights into the occurrence of ADEs following tirzepatide administration, potentially supporting clinical monitoring and risk identification efforts.